2017
DOI: 10.1111/jgs.15216
|View full text |Cite
|
Sign up to set email alerts
|

Individualizing Prevention for Older Adults

Abstract: Prevention can help older adults avoid illness by identifying and addressing conditions before they cause symptoms, but prevention can also harm older adults if conditions that are unlikely to cause symptoms in the individual's lifetime are identified and treated. To identify older adults who preventive interventions are most likely to benefit (and most likely to harm), we propose a framework that compares an individual's life expectancy (LE) with the time to benefit (TTB) for an intervention. If LE is less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 41 publications
(70 reference statements)
0
55
0
Order By: Relevance
“…Consider patients' health trajectory: While there are few predictive tools to address prognosis for outcomes such as function or quality of life, consider likely changes over 1 to 2 years. Lack of return to prehospital function predicts poor health trajectory Estimate lag time (time horizon) to benefit: Time to benefit for treatments (lag time) may be longer than the individual's projected life span, and varies for different interventions Consider time frames of 1 to 2, 2 to 5, 6 to 10, and 10 or more years …”
Section: Actions and Action Steps For Care Of Older Adults With Mccsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consider patients' health trajectory: While there are few predictive tools to address prognosis for outcomes such as function or quality of life, consider likely changes over 1 to 2 years. Lack of return to prehospital function predicts poor health trajectory Estimate lag time (time horizon) to benefit: Time to benefit for treatments (lag time) may be longer than the individual's projected life span, and varies for different interventions Consider time frames of 1 to 2, 2 to 5, 6 to 10, and 10 or more years …”
Section: Actions and Action Steps For Care Of Older Adults With Mccsmentioning
confidence: 99%
“…Estimate lag time (time horizon) to benefit: Time to benefit for treatments (lag time) may be longer than the individual's projected life span, and varies for different interventions Consider time frames of 1 to 2, 2 to 5, 6 to 10, and 10 or more years …”
Section: Actions and Action Steps For Care Of Older Adults With Mccsmentioning
confidence: 99%
“…A detailed discussion of this topic is beyond the scope of this review, although we will highlight some methods that have been proposed. It has been suggested that life tables (which account for persons who may be more or less healthy than average, based on the presence of multiple co‐morbidities and/or functional impairment, for example) can be used for insight into life expectancy . One study in our review categorized persons as having limited life expectancy based on the NECPAL CCOMS‐ICO tool .…”
Section: Discussionmentioning
confidence: 99%
“…One study in our review categorized persons as having limited life expectancy based on the NECPAL CCOMS‐ICO tool . Mortality indices and online calculators have also been suggested as ways to estimate life expectancy in the context of medication decisions . Finally, the “surprise question” (Would you be surprised if this patient died in the next 12 months?)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation